TEORI KEAGENAN DAN MANAJEMEN LABA DARI SUDUT PANDANG ETIKA MANAJER - Luayyi, Sri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
This paper discuss about how agency theory in perspective attitude. If we clarify about agency theory so in discussing cannot separated with behavior of manager in doing earning management, because earning management is one of way that doing by manager in order to maintaining of achievement in front of principal in the most society consider that earning management is legality action, not harming another side and enabled (deed of manager heaving the character of positive), but in their action earning management is often to behavior of manager heaving the character of negative, here the problem is how the manager can differences among practice of earning management that bring the negative influence (it means that we must avoid) and how we can practicing earning management and bring it in positive influence (it means we can do it). In the general of main side of this paper is in the agency theory have explain about the relation between agent and principal. In the practice is manager as organizer of company will more known about the information internal and external related to present day company prospect and a period of come to be compared owner of company. So the information came to be the owner of company some time in appropriate within the fact of condition, that condition is familiar with term information asymmetry. In the information asymmetry both of them will giving opportunity for manager to do earning management.. Manager only will doing earning management that positive character if they have the good attitude, because basically manager that they have the good attitude always acting what conscience word so each every decision and step of will express ethical behavior.Keywords : Agency Theory, Earning Management, Manager Attitude